Land conversion to cement factory and mining: Effect of environmental change to disaster and farmer livelihoods - Harifuddin, Harifuddin; Haris, Subhan; Anriani, Haslinda B; Azuz, Faidah; Apriningsih, Apriningsih (Brawijaya University, 2024)
Land conversion from agricultural to cement factory and mining areas has consequences for environmental change and degradation that cause disasters and sustainability farmer livelihood. This study aimed to analyze land conversion to a cement factory and mining as determinants of environmental change, environmental change as a determinant of environmental degradation, and the effect of environmental change and environmental degradation on the sustainability of farmer livelihoods. This research used a sequential explanatory design or quantitative rather than qualitative. The research sample totaled 183 respondents. Data collection used the quantitative stage using questionnaires and the qualitative stage using in-depth interviews, observation, and literature study. The results showed that land conversion to a cement factory and mining are causes of environmental change, followed by environmental degradation, such as factory smoke pollution, dust from karst mines, factory vehicle dust, and soil pollution due to coal piles. Environmental change is a cause of environmental degradation, such as crop failure, acute respiratory illness, land clearing, and flooding. The effect of environmental change and environmental degradation on the sustainability of farmer livelihoods is that almost all farmers sell their rice fields for the factory area, then buy ponds, do business, open stalls, and open photocopy businesses. No one returned to being a farmer. The conversion of agricultural land to a cement factory and mining caused a decrease in environmental functions, namely the disruption of the ecosystem chain, which caused flooding and acute respiratory disease and caused farmers to switch to non-agricultural livelihoods.